Comparative study on the behaviour of textile reinforced concrete slab with engineered cementitious composite slab. (2020) - Chinnasamy, M.; Ajithkumar, R.; Singh, Anisha; Yangzom, Dorjee; Parvati, T.S.; Joanna, P.S.
Abstract: This paper presents the flexural behaviour of slabs made with Engineered Cementitious Composite (ECC) and Glass Fibre Reinforced Polymer (GFRP) concrete. Engineered Cementitious Composites (ECC) are a special category of fibre-reinforced composites that has attracted significant interest in research and engineering applications because of its high tensile properties. In this investigation, ECC slab is made with High-Volume Fly Ash (HVFA) an eco-friendly material, cement, manufactured sand, micro silica and Polyvinyl Alcohol (PVA) fibre and the GFRP slab is made with ordinary concrete reinforced with GFRP mesh. Experimental results such as load – deflection relationship, ultimate load carrying capacity and load – strain relationship of the specimens are presented. It is found that the ultimate load carrying capacity of the GFRP slab is more than the ECC slab. Thus, reinforcing the slab with GFRP will be a better alternative as compared to ECC slab construction.